KARAKTERISTIK PEMIMPIN NASIONAL IDEAL MENURUT PEMILIH PEMULA YOGYAKARTA - Ryan Sugiarto (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2014)
National leadership succession through general election is the foundational schema for the state management and change. The coming leadership hope bring good transformation. This research aimed to understand and analyzed how the characteristic of ideal national leader according to beginning voter in Yogyakarta. With using the survey there are 712 participant. Respondent consist of 352 male 360 female which distribute in all district at Yogyakarta province. With the sample error 3,6% and the trust level 95%. The sample take by multi stage random sampling, at 5 local district at Yogyakarta. Data take at September, 26 until October, 4 2013. Triangulation data be driven by interview. The result show that beginning voter at Yogyakarta aspire the idealistic national leader which is professional, from the cipil, youth leader and nationals.